Quality of care in public sector family planning services in KwaZulu-Natal, South Africa: a qualitative evaluation from community and health care provider perspectives - Yolandie Kriel; Cecilia Milford; Joanna Paula Cordero; Fatima Suleman; Petrus S. Steyn; Jennifer Ann Smit (BMC, 2021)
Abstract Background Quality of care is a multidimensional concept that forms an integral part of the uptake and use of modern contraceptive methods. Satisfaction with services is a significant factor in the continued use of services. While much is known about quality of care in the general public health care service, little is known about family planning specific quality of care in South Africa. This paper aims to fill the gap in the research by using the Bruce-Jain family planning quality of care framework. Methods This formative qualitative study was conducted in South Africa, Zambia, and Kenya to explore the uptake of family planning and contraception. The results presented in this paper are from the South African data. Fourteen focus group discussions, twelve with community members and two with health care providers, were conducted along with eight in-depth interviews with key informants. Thematic content analysis using the Bruce-Jain Quality of Care framework was conducted to analyse this data using NVIVO 10. Results Family planning quality of care was defined by participants as the quality of contraceptive methods, attitudes of health care providers, and outcomes of contraceptive use. The data showed that women have limited autonomy in their choice to either use contraception or the method that they might prefer. Important elements that relate to quality of care were identified and described by participants and grouped according to the structural or process components of the framework. Structure-related sub-themes identified included the lack of technically trained providers; integration of services that contributed to long waiting times and mixing of a variety of clients; and poor infrastructure. Sub-themes raised under the process category included poor interpersonal relations; lack of counselling/information exchange, fear; and time constraints. Neither providers nor users discussed follow up mechanisms which is a key aspect to ensure continuity of contraceptive use. Conclusion Using a qualitative methodology and applying the Bruce-Jain Quality of Care framework provided key insights into perceptions and challenges about family planning quality of care. Identifying which components are specific to family planning is important for improving contraceptive outcomes. In particular, autonomy in user choice of contraceptive method, integration of services, and the acceptability of overall family planning care was raised as areas of concern.